Prevalence of dysmenorrhea in students of higher education institution in Piauí (Research, Society and Development, 2022)
Introduction: Primary dysmenorrhea (PD) is characterized as pain in the abdominal region during the menstrual period in the absence of pelvic pain, and may be associated with other symptoms such as lower back pain, nausea, fatigue, headache, among others. Objective: To investigate the number of students who present primary dysmenorrhea in a Higher Education Institution. Methods: It is a field study, observational, cross-sectional, quantitative in nature. The instrument used to collect data consisted of a questionnaire through the Google Forms platform, whose link was sent via WhatsApp to the disciplines through two coordinators of two courses, professors and group leaders. Applied in the following order: Triage Form, Informed Consent Term (ICF) and finally, the questionnaire. Results: 209 students responded to the questionnaire. The prevalence of PD was 90% among the research participants. The most common associated symptoms are irritability, fatigue, and pain irradiation to the lombar region. It is also evident that PD and its symptoms interfere with the performance of daily activities, negatively impacting the quality of life of women, contributing to the increase in school absenteeism. Conclusion: A high prevalence of PD was found among the research participants. Apart from dysmenorrhea, the most predominant symptoms are: irritability, fatigue and irradiation of pain to the lombar region. These interfere in the quality of life of women.